Large declines in organofluorine contamination indicated by subarctic marine mammal tissues - Jennifer M. Sun; Euna Kim; Heidi M. Pickard; Bjarni Mikkelsen; Katrin S. Hoydal; Halla W. Reinert; Colin P. Thackray; Elsie M. Sunderland (Proceedings of the National Academy of Sciences, 2026)
The ocean is thought to be the terminal sink for per- and polyfluoroalkyl substances (PFAS), persistent organofluorine chemicals used widely in modern commerce for decades. Industry and stewardship programs phased out the most abundantly produced legacy PFAS in the early 2000s due to toxicity concerns. However, they have since been replaced by shorter carbon chain and “novel” chemistries, and past work hypothesized likely increases in these replacement PFAS that were not previously quantifiable. To address this gap, we measured bulk extractable organofluorine (EOF) in archived liver and muscle tissues from pelagic Subarctic pilot whales over the last several decades. Results show EOF concentrations peaked in 2011 and declined by over 60% by 2023. Among a broad suite of targeted and suspect PFAS measured using high-resolution mass spectrometry, only one was consistently increasing through 2023. Tissue concentrations of four main legacy PFAS that accounted for over 75% of EOF were all decreasing by 2023. The timing of peak concentrations depended primarily on whether they were transported to the subarctic by ocean circulation or atmospheric deposition, with the latter declining much faster. Oceanic transport and bioaccumulation modeling suggests that decadal-scale lags between production and food web bioaccumulation are primarily driven by marine transport processes. Large declines in tissue concentrations in this study reinforce the effectiveness of phase-outs in chemical production. However, other work showing stable or increasing EOF in human serum suggests many emerging PFAS with more neutral physicochemical properties may be preferentially accumulating in terrestrial and nearshore environments compared to legacy PFAS.